A Test of the Extended Functional Fixation Hypothesis. - Hand, John R.M. (The Accounting Review, 1990)
Proposes and tests a probabilistic extension of the efficient market hypothesis toward the functional fixation hypothesis (FFH). Calendar time positioning of the swap announcement and swap quarter's earnings; Debt-equity swaps as a test of extended FFH (EFFH); Empirical methods.